PENERAPAN THOUGHT STOPPING THERAPY UNTUK MENURUNKAN TINGKAT KECEMASAN PADA PASIEN POST OPERATIVE SECTIO CAESAREA DENGAN BAYI PREMATUR DI BANGSAL TERATAI 1 RSUD KARTINI KARANGANYAR - Bintarasari, Senja; Mardiah, Adriana (Sekolah Tinggi Ilmu Kesehatan Mitra Husada Karanganyar, 2025)
Anxiety is a common psychological problem experienced by mothers after undergoing a cesarean section, especially when the baby is born prematurely and requires care in the Neonatal Intensive Care Unit (NICU). This separation condition can cause worry, helplessness, and may trigger postpartum blues and depression. This study aims to describe the application of Thought Stopping Therapy as a non-pharmacological intervention to reduce anxiety levels in post-cesarean section patients with premature babies. The method used was a case study on 1 post-cesarean section patient in Teratai 1 Ward of RSUD Kartini Karanganyar, conducted for 3 days with a duration of 10 minutes per therapy session. Data were collected through interviews, observations, and anxiety level measurements using the HARS questionnaire. The results showed a decrease in anxiety levels from severe (score 41) to mild (score 14) after therapy. Thought Stopping Therapy was effective in helping patients control negative thoughts and replace them with positive thoughts, thereby reducing both physiological and psychological symptoms of anxiety.